University credentials and wage differentials in the Argentine productive structure - Trombetta, Martín; Pascuariello, Gisella; Sidicaro, Nicolás; Sonzogni, Pablo; Trebotic, Gisel (Estudios de Economía, 2022)
We estimate the wage return of the different university-level educational credentials in Argentina using administrative data for 2019. The results indicate sizeable variability according to the hierarchy of the degree and area of knowledge. Applied Sciences obtain the best results, while the opposite is true for the Humanities. These effects are higher for individuals located in the right tail of the conditional wage distribution.